Analysis of Cloud Growth Phases When Nocturnal Hail Occurs (Case Study: Sekadau, 22 August 2020) - Rayhan Rinanto; Ni Putu Risna Purwandari; Yosafat Donni Haryanto (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2023)
On August 22 2020, hail was reported in Sekadau, West Kalimantan at 21:23 WIB. The phenomenon of hail does not usually occur at night. So, further research is needed to find out how the cloud growth phase and Cumulonimbus (Cb) cloud structure are in this phenomenon. This research utilizes remote sensing instruments in the form of a C-Band type weather radar for the Supadio Meteorological Station and the Himawari 8 Satellite, as well as a radiosonde instrument that is closest to the time and location of the hail events. The results of satellite imagery show that nocturnal hail occurs before the clouds reach the mature phase, with the cloud top temperature at the time of hail less than -60 ºC. The maximum reflectivity detected by the radar using CMAX products shows a less significant value with an intensity of up to 52 dBZ. The VCUT product shows the maximum intensity altitude is at an altitude of 5 – 8 km. This shows that there is a process of ice condensation on the freezing level layer. The ZHAIL product image shows that there is a potential for hail in the Sekadau area with a probability of more than 80%. The occurrence of ice rain at Sekadau at night is caused by the presence of Cumulonimbus clouds with very cold peak temperatures and the mixing process above the freezing level which supports the formation of ice condensation in Cb clouds.